Risk of Premature Birth in Pregnant Women Infected with COVID-19: A Meta Analysis - Purnasari, Ratih Hermas; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2022)
Background: Pregnancy is a state of great susceptibility to infectious diseases, and it is not surprising that viral infections can affect pregnancy outcomes. COVID-19 infection during pregnancy is considered a risk factor for adverse outcomes such as, preterm delivery. This study aimed to analyze the risk of preterm delivery in pregnant women with COVID-19. Subjects and Method: This study was conducted using a systematic review and meta-analysis. Article searches were conducted using electronic databases such as Google Scholar, PubMed, and Scopus. The articles used are articles published from 2020-2021. The keywords used to retrieve the articles were: [(COVID-19 OR 2019-nCoV OR “novel coronavirus” OR SARS-CoV-2 OR “coronavirus 2”) AND (“preterm birth” OR preterm OR “preterm delivery”)] . The inclusion criteria used were full paper with observational studies (retrospective or prospective cohorts), multivariate analysis with Adjusted Odd Ratios (aOR), study subjects were pregnant women who were confirmed to be infected with COVID-19, comparison were pregnant women who were negative for COVID-19, outcome study was preterm birth (<37 weeks). The article search results are listed in the PRISMA diagram and analyzed using the Review Manager 5.3 . application. Results: A total of 10 articles from Iran, France, Bangladesh, Spain, the United States, Romania, the United Kingdom and China showed that the heterogeneity of the primary studies in the meta-analysis was low (I2= 4%; p= 0.40), therefore this study used a fixed effect model. The results showed that the risk of premature birth in pregnant women infected with COVID-19 was 2.18 times that of pregnant women not infected with COVID-19 (aOR=2.18; 95% CI=2.00 to 2.37) and statistically significant (p<0.001). Conclusion: Higher risk of preterm birth in pregnant women with COVID-19.